The Greek Law on Strategic Investments in Light of the FDI Screening Regulation: Will the Greek Investment Regime’s Openness Endure? - Fotopoulos, Dionysis N. (HAPSc Policy Briefs Series, 2022)
Attracting Foreign Direct Investment (FDI) is vital for Greece’s growth in the aftermath of a lengthy economic crisis and the Covid-19 pandemic. Concurrently, the European Union (EU) seeks to safeguard essential bloc-wise security interests that are compromised by third country investors, especially Chinese ones, sprawling across member states – a policy concern substantiated in normative text as recently as 2019 by the enactment of Regulation 2019/452. The latter set the basic pan-European contour in terms of member states’ cooperation for the screening of FDI. A year later, the Greek Parliament voted for Law 4864/2021 on Strategic Investments, with a view to incentivizing aspiring high-profile investors. In that regard, the main objective of the present policy paper is to examine how Law 4864/2021 interplays with Regulation 2019/452. The paper will conclude that the Greek liberalized framework will have to align in the future with the European trend of extended screening over FDI, notwithstanding Law 4864/2021 moving into the opposite direction.